Believing in climate change, but not behaving sustainably: Evidence from a one-year longitudinal study. (April 2018) - Hall, Michael P.; Lewis, Neil A.; Ellsworth, Phoebe C.
Abstract: We conducted a one-year longitudinal study in which 600 American adults regularly reported their climate change beliefs, pro-environmental behavior, and other climate-change related measures. Using latent class analyses, we uncovered three clusters of Americans with distinct climate belief trajectories: (1) the "Skeptical, " who believed least in climate change; (2) the "Cautiously Worried, " who had moderate beliefs in climate change; and (3) the "Highly Concerned, " who had the strongest beliefs and concern about climate change. Cluster membership predicted different outcomes: the "Highly Concerned" were most supportive of government climate policies, but least likely to report individual-level actions, whereas the "Skeptical" opposed policy solutions but were most likely to report engaging in individual-level pro-environmental behaviors. Implications for theory and practice are discussed. Highlights: We conducted a one-year longitudinal study of 600 Americans' climate beliefs. Cluster analyses found three distinct groups based on climate belief trajectories. Climate change believers were most likely to endorse federal climate policies. Climate change skeptics were most likely to report pro-environmental behavior.